Contingency of Necessity and Necessity of Contingency.Reason, System and Freedom in Meillassoux and Hegel (Itinera, 2015)
Aim of this paper is to investigate contingency and totality as the ontological conditions of possibility of improvisation. Through a critical analysis of Quentin Meillassoux's argument about the necessity of contingency and the impossibility of totality, I will try to show that Hegel's logic is actually able to show some limits of Meillassoux's theory, and to prove that totality is also necessary in order to properly think improvisation.